Can bees deter elephants from raiding crops? An experiment in the communal lands of Zimbabwe - Karidozo, Malvern; Osborn, Ferrel (Pachyderm, 2005)
This project in the Lower Guruve District in northern Zimbabwe sought to explore the hypothesis put forth by Vollrath nd Douglas-Hamilton. In Samburu/Laikipia area of Kenya they 'observed that elephants did not feed on trees with hives and trees prone to elephant damage experienced no furhter damage'. (Vollrath and Douglas-Hamilton. 2002) The earlier researchers suggested that besides the protection factor keeping bees could provide economic returns by harvesting the honey. The Lower Guruve District is under going rapid agricultural expansion but still contains a high and mobile elephant population. To test the effectiveness of bees in deterring elephants, hives were placed near entrances to maize, cotton and sorghum fields, along elephant paths to these fields and near paths to waterpoints in gardens. selected maizeand sorghum plots were visited 5 times a week for 6 months, and wherever field visits were made the observer recorded any activity between any elephant present and the bees from the nearby hives. 58 incidents of crop damage were recorded. 79% of the damage was done by bulls, 14% by cows and 7% by mixed herds. 59% of the damage was done to crops in their growing stage while 41% was done to crops in their mature stage. Maize was the most often damaged crop. This study found no significant difference between fields damaged with bees/hives and without bees/hives. However, it was noted that elephants avoided entrances to fields in plots near bee hives. Elephants tended not to use paths to waterpoints when hives had been placed but made new paths to these waterpoints. When hives were placed along paths in a forested area heavily used by elephants the elephants moved away from this area. Although this study did not find bees were deterred from raiding crops the authors tend to support the hypothesis of the earlier study.